Experimental infection of Phlebotomus perniciosus and Phlebotomus tobbi with different Leishmania tropica strains - Vaselek, Slavica; Volf, Petr (International journal for parasitology, 2019)
Cutaneous leishmaniasis due to Leishmania tropica is increasingly documented in Europe and the Middle East. Besides its specific vector, Phlebotomus sergenti, permissive Phlebotomus sand flies are suspected as potential vectors of L. tropica. We investigated the susceptibility of two widely distributed species, Phlebotomus perniciosus and Phlebotomus tobbi. Laboratory-reared sand flies were infected experimentally with L. tropica strains differing in lipophosphoglycan epitopes, geographical distribution and epidemiology. High infection rates, heavy parasite loads and fully developed late-stage infections including colonization of the stomodeal valve were observed in all parasite-vector combinations. Our findings demonstrate that P. perniciosus and P. tobbi are susceptible to different L. tropica strains and may play a role in their circulation in endemic foci of Europe, the Middle East and North Africa.
Keywords: Phlebotomus tobbi; Phlebotomus perniciosus; Insect Vectors; Leishmania tropica; Transmission; hostitelská specificita; Parasite Load; Animals; parazitární zátěž; Phlebotomus; hmyz - vektory; Host Specificity; zvířata; Animal Structures; anatomické struktury zvířat